What drives university research performance? An analysis using the CWTS Leiden Ranking data. Issue 3 (August 2017) - Frenken, Koen; Heimeriks, Gaston J.; Hoekman, Jarno
Highlights: We assess university performance by size, age, city size, specialization, and country. Differences in university performance mainly stem from size and country location. Benchmarking is meaningful among universities of similar size and countries. No country excels at impact, internationalization and innovation simultaneously. Abstract: This paper analyzes the factors underlying university research performance as indicated by the number of highly-cited publications, international co-publications, and university-industry co-publications. The three performance indicators evaluate three possible university missions, respectively: research excellence, internationalization, and innovation. Using a regression analysis, we assess to what extent a university's research performance is influenced by structural variables including size, age, city size, location in a capital city, disciplinary orientation, and country location. Our results show that research performance differences among universities mainly stem from size, disciplinary orientation and country location. This suggests that simple global benchmarking can be misleading; rather, benchmarking is most meaningful between universities of a similar size supplemented with contextual information on a university's specific mission, orientation and national institutions.